Protective role of cytoplasmic p21Cip1/Waf1 in apoptosis of CDK4/6 inhibitor‐induced senescence in breast cancer cells. (11th November 2021) - Kartika, Irna D.; Kotani, Hitoshi; Iida, Yuichi; Koyanagi, Akira; Tanino, Ryosuke; Harada, Mamoru
Abstract: Inhibition of CDK4/6 slows the cell cycle and induces senescence in breast cancer cells. However, senescent cancer cells promote invasion and metastasis. Several drugs reportedly target senescent cells, including ABT‐263 (navitoclax). We examined the effects of the CDK4/6 inhibitor abemaciclib and ABT‐263 on two human breast cancer cell lines. The abemaciclib and ABT‐263 combination additively decreased the viability of MDA‐MB‐231 cells, but not MCF‐7 cells. Also, the combination therapy‐induced caspase‐dependent apoptosis in MDA‐MB‐231 cells. Combination therapy with abemaciclib and ABT‐737, an ABT‐263 analog, significantly suppressed the in vivo growth of MDA‐MB‐231 with transient body‐weight loss. Given that p16 Ink4a and p21 Cip1/Waf1 are key factors in senescence and that both cell lines were negative for p16, the role of p21 in apoptosis of treated breast cancer cells was investigated. Although abemaciclib increased the cytoplasmic p21 level in both cell lines as a hallmark of senescence, the abemaciclib and ABT‐263 combination decreased it only in MDA‐MB‐231 cells. This decrease of p21 expression was relieved by caspase inhibition, and p21 was colocalized with caspase‐3 in the cytoplasm of MDA‐MB‐231 cells. Alternatively, small interfering RNA‐mediated knockdown of p21 rendered caspase‐3‐negative MCF‐7 cells susceptible to abemaciclib and ABT‐263, as well as TNF‐related apoptosis‐inducing ligand. Furthermore, a clinical database analysis showed that p21 high breast cancer patients had a poorer prognosis compared to p21 low patients. These results suggest that cytoplasmic p21 plays a protective role in apoptosis of CDK4/6 inhibitor‐induced senescent breast cancer cells. Abstract : Colocalization of p21 and caspase‐3 in treated MDA‐MB‐231 breast cancer cells.